Body mass index and basal androstenedione are independent risk factors for miscarriage in polycystic ovary syndrome - Wan Yang; Rui Yang; Mingmei Lin; Yan Yang; Xueling Song; Jiajia Zhang; Shuo Yang; Ying Song; Jia Li; Tianshu Pang; Feng Deng; Hua Zhang; et al. (BMC, 2018)
Abstract Background There is limited literature investigating the effects of body mass index (BMI) and androgen level on in vitro fertilization (IVF) outcomes with a gonadotropin-releasing hormone (GnRH)-antagonist protocol in polycystic ovary syndrome (PCOS). Androgen-related variation in the effect of body mass index (BMI) on IVF outcomes remains unknown. Methods In this retrospective study, 583 infertile women with PCOS who underwent IVF using the conventional GnRH-antagonist protocol were included. Patients were divided into four groups according to BMI and androgen level: overweight- hyperandrogenism(HA) group, n = 96, overweight-non-HA group, n = 117, non-overweight-HA group, n = 152, and non-overweight-non-HA group, n = 218. Results A significantly higher number of oocytes were retrieved, and the total Gn consumption as well Gn consumption per day was significantly lower, in the non-overweight groups than in the overweight groups. The number of available embryos was significantly higher in the HA groups than in the non-HA groups. Clinical pregnancy rate was of no significant difference among four groups. Live-birth rates in the overweight groups were significantly lower than those in non-overweight-non-HA group (23.9, 28.4% vs. 42.5%, P<0.05). The miscarriage rate in overweight-HA group was significantly higher than that in non-overweight-non-HA group (45.2% vs. 14.5%, P<0.05). Multivariate logistic regression analysis revealed that BMI and basal androstenedione (AND) both acted as significantly influent factors on miscarriage rate. The area under the curve (AUC) in receiver operating characteristic (ROC) analysis for BMI and basal AND on miscarriage rate were 0.607 (P = 0.029) and 0.657 (P = 0.001), respectively, and the cut-off values of BMI and basal AND were 25.335 kg/m2 and 10.95 nmol/L, respectively. Conclusions In IVF cycles with GnRH-antagonist protocol, economic benefits were seen in non-overweight patients with PCOS, with less Gn cost and more retrieved oocytes. BMI and basal AND were both significantly influential factors with moderate predictive ability on the miscarriage rate. The predictive value of basal AND on miscarriage was slightly stronger than BMI.